Effect of E-Commerce Use in Consumptive Behavior of Students Madiun State Polytechnic - Netty Lisdiantini; Bias Nur Elmira; Farida Tri Hastuti (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The development of technology and information is currently very influential in all aspects of life, for example the use of social media is not only used as a means of obtaining information but social media is widely used as a means of doing business call an online shop. The development of technology, there are many online buying and selling sites where in it gathers many online shops into one site that makes it easier for buyers to get the items they want with various promos that attract students to shop on the site. In this study, researchers want to know how the development of E-Commerce affects the consumptive behavior of Madiun State Polytechnic students. The method used in this study is descriptive qualitative method with a sample of 105 Madiun State Polytechnic students by distributing questionnaires. The results show that of the 105 samples taken, it can be seen that the biggest influence on students' consumptive behavior towards E-commerce is due to the promo or discount factor provided by E-commerce sites at the beginning of the month.